PROMOTION MIX NAHDLATUL ULAMA UNIVERSITY OF SURABAYA TO INCREASE NEW STUDENT’S INTEREST - Kristanto, Joko; Soleh, Achmad Khudori; Al-Idrus, Salim; Raya, Moch Khafidz Fuad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
The mushrooming number of PTKI (Perguruan Tinggi Keagamaan Islam - Islamic Religious Higher Education) clusters has made competition between universities even tighter, thus using promotional strategies to increase public trust. The increase in the interest of new students is an indicator of the success of the college in marketing education. This research is devoted to UNUSA as an Islamic organization-based PTKI (NU) that carries out promotional strategies to increase the interest of new students. This research uses a qualitative case study approach. The results showed that UNUSA used a promotion mix through advertising, such as; national television, personal selling, publications, and direct marketing. UNUSA's branding as PTNU (Nahdlatul Ulama' College) using a promotion mix has implications for increasing the number of new students by 21% over the last five years with a total achievement of 6,035 new students from 49% of the Nahdliyin community segment.